Kombinasi Metode Swara dan Smart dalam Sistem Pendukung Keputusan Pemilihan Guru Berprestasi Pada SMPN 6 Janapria - Srihati, Ania; Murniati, Wafiah; Mutawalli, Lalu (Jurnal Ilmiah Global Education, 2025)
Outstanding Teachers are educators who have superior performance in pedagogical, personal, social, and professional competencies that meet or even exceed National Education Standards. The Selection of outstanding teachers is important in improving the quality of education in schools. However, a manual selection process can result in unfairness in the assessment. Therefore, this research aims to make it easier for school principals to select outstanding teachers, namely by combining the multi-criteria method Stepwise Weight Assessment Ratio Analysis (SWARA) and Simple Multi-Attribute Rating Technique (SMART) in assessing and selecting teachers with the best quality at SMPN 6 Janapria. This research involved 16 teachers as alternatives being evaluated, with respondents consisting of principals, deputy principals, and class leaders from levels one, two, and three. The SWARA method was used to determine the weight of criteria according to their level of importance. Meanwhile, the SMART method is used to rank each alternative based on the weights that have been determined late. This research shows that this method can provide a more systematic and transparent selection process. Based on the ranking results, the teacher who received the highest score was Teacher HK with a score of 0.969, followed by Teacher ML with a score of 0.772, and Teacher RM with a score of 0.731. By implementing a decision support system based on the SWARA and SMART methods, the process of selecting outstanding teachers can be carried out more fairly and objectively. This approach is expected to help schools carry out assessments and select teachers who have the best performance based on validated data and criteria.